2014
DOI: 10.30958/ajte.1-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the ACI-DAfStb Database of Shear Tests on Slender Reinforced Concrete Beams without Stirrups for Investigations on the Shear Capacity Scatter

Abstract: The shear transfer mechanism of RC slender members without stirrups still presents very high uncertainties and the question has generated many controversies and debates since the beginning of the last century. Regrettably, until now the real causes of this problem are not yet clear to the scientific community and the issue is still important to investigate, especially nowadays that the minimizing of natural resources is of uppermost global interest. Due to the increased laboratory costs, actual studies are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 16 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…A total of 13 groups of shear tests on comparable slender RC beams without stirrups extracted from the ACI‐DAfStb evaluation database (the reader should refer to for details) and grouped by Sangiorgio et al were identified and considered for the subsequent analysis.…”
Section: The Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 13 groups of shear tests on comparable slender RC beams without stirrups extracted from the ACI‐DAfStb evaluation database (the reader should refer to for details) and grouped by Sangiorgio et al were identified and considered for the subsequent analysis.…”
Section: The Methodologymentioning
confidence: 99%
“…shows that, for each of the three models, predictions cover the range of observed shear strength in a satisfactory manner. In particular, the figure shows the comparison of the box plots of V test measured for groups 3, 5 and 12 of comparable experiments (notation according to ) and V R,c,θ evaluated with the three models A, B and C. A box plot is a statistical technique used to summarize and compare groups of data visually. In each box, the central mark is the median, the edges of the box are the 25th and 75th percentiles, the whiskers extend to the most extreme data points not considered outliers and outliers are plotted individually.…”
Section: The Methodologymentioning
confidence: 99%
See 3 more Smart Citations